Comparison Between the Efficacies of Amlodipine and Cilnidipine in Treating Hypertensive Patients - Hasan, Md. Hasibul (Cardiology and Cardiovascular Medicine, 2024)
Background: Amlodipine and cilnidipine, both Calcium Channel Blockers (CCBs), possess distinct pharmacokinetic and pharmacodynamic properties. Yet, there's a notable lack of comprehensive research on their effectiveness in treating hypertension. This gap hinders our understanding of their therapeutic potential and comparative efficacy. Aim of the study: The aim of the study was to compare the efficacies of amlodipine and cilnidipine in treating hypertensive patients. Methods: This cross-sectional observational study was conducted at the Department of Cardiology, Mugda Medical College & Hospital, Dhaka, Bangladesh, spanning from January 2021 to December 2021. The study enrolled 140 diagnosed hypertensive patients, aged 20 to 65, of both genders. Patients were divided into two groups: Amlodipine (70 patients) and Cilnidipine (70 patients). Random sampling was employed for sample selection, and data were collected using a semi-structured predesigned questionnaire. Data analysis utilized MS Office tools and SPSS Version 23.0. Results: Over 8 weeks, Amlodipine decreased mean systolic blood pressure (SBP) from 151.26 to 133.12 and diastolic blood pressure (DBP) from 95.9 to 86.3. Similarly, Cilnidipine lowered mean SBP from 149.25 to 130.09 and DBP from 94.11 to 84.86. Both drugs had minimal impact on pulse rate. Amlodipine reduced mean pulse rate from 74.74 to 74.02 and Cilnidipine reduced from 76.8 to 75.43. Conclusion: Both Amlodipine and Cilnidipine are effective drugs for controlling systolic and diastolic blood pressure. However, in addition to blood pressure control, Cilnidipine exhibits a slight advantage over Amlodipine in reducing heart rate and pulse rate.